2020
DOI: 10.3390/healthcare8020161
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Methicillin Susceptible and Resistant Staphylococcus aureus Nasal Carriage and Its Antibiotic Sensitivity among Basic and Clinical Years Medical Students

Abstract: Background: Healthcare workers (HCWs) and medical students can be asymptomatic carriers in transmitting methicillin resistant and susceptible Staphylococcus aureus (MRSA and MSSA). Studying epidemiological and antibiotic susceptibility data is necessary to limit the spread of infections, help with treatment and understand the transmission dynamics of MSSA and MRSA. Our study assessed the rate of MSSA and MRSA nasal carriage and its antibiogram among medical students in basic and clinical years at the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…According to Chen et al (2012), the prevalence of MRSA in preclinicals was 2.4% while clinical was 1.9% after 1 to 2 years of exposure. In the study by Alzoubi et al (2020), MRSA was found in 1.9% of students in preclinical years and 2.8% among clinical years, but the years of each cycle were not distinguished. Whereas in two studies, no MRSA cases were found (Gualdoni et al, 2012;Syafinaz et al, 2012).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…According to Chen et al (2012), the prevalence of MRSA in preclinicals was 2.4% while clinical was 1.9% after 1 to 2 years of exposure. In the study by Alzoubi et al (2020), MRSA was found in 1.9% of students in preclinical years and 2.8% among clinical years, but the years of each cycle were not distinguished. Whereas in two studies, no MRSA cases were found (Gualdoni et al, 2012;Syafinaz et al, 2012).…”
Section: Resultsmentioning
confidence: 90%
“…In 2011, MRSA infections were estimated to account for about 50-63% of all nosocomial infections in the United States (Chamberlain & Singh, 2011). The current percentage of MRSA among S. aureus has been increasing, however, worldwide, it varies by region, corresponding to rates of 20 to 80% of all S. aureus (Alzoubi et al, 2020). In South America, North America, Malta and Asia, MRSA prevalence rates were greater than 50%.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations